The regulation of erythropoietin and other genes by hypoxia: The search for universal mechanisms - Gleadle, Jonathan M. (Acta Andina, 2025)
Oxygen is of fundamental importance for living organisms. In higher organisms it plays a vital role in energy provision by acting as the terminal accpetor in the electron transport chain. It also has an essential role in many critical biosynthetic reactions. Despite performing these vital functions, oxygen can exert toxic effects because of the formation of reactive oxygen species. Achieving the appropriate delivery of oxygen to tissues and cells, adjustin metabolism accordingly and minimising the toxicity of oxygen is crucial for living organisms. In order for this to occur, organisms must be able to sense oxygen and respond to changes in oxygen tension by altering the expression of particular genes. In single cellullar organisms, oxygen is obtained from the environment by simple diffusion. In larger, multicellular organisms, complex organs are necessary to supply oxygen to tissues. In mammals oxygen is absorded by the lungs into the blood. Oxygen has a relatively poor aqueous solubility. To achieve sufficient oxygen supply to the tissues, oxygen carriage in the blood is considerably enhanced by the transport of oxygen liganded to haemoglobin, packaged within red blood cells. A complex vasculature enables the delivery of this oxygenated blood to the tissues. In order for this supply to be optimally maintained, precise distribution of the vasculature to the lungs and other tissues is essential, as is the control of ventilation and red blood cell production.